2020
DOI: 10.7717/peerj.9263
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of methods used for 3-dimensional superimposition of craniofacial skeletal structures: a systematic review

Abstract: Background So far, several techniques have been recommended for the assessment of craniofacial changes through skeletal tissue superimposition, but the evidence that supports them remains unexplored. The purpose of the present study is to assess the available literature on skeletal-tissue superimpositions of serial craniofacial CT or CBCT images used to detect morphological changes. Materials and Methods Medline (via Pubmed), EMBASE, Google… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…Here, the CBCT derived facial surface models were used to assess the outcomes of 3D facial image superimposition techniques as related to the internal skeletal con guration. It has been shown that CBCT derived facial soft-tissue surface models are quite similar to those obtained by stereophotogrammetry 13,43,44 , allowing the assessment of changes in facial morphology in regards to standard reference structures, namely the anterior cranial base 3,4,8,18 . Thus, through the comparison with well-established anterior cranial base superimposition techniques 3,4,8,18 , the performance of the surfacebased techniques was thoroughly assessed.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Here, the CBCT derived facial surface models were used to assess the outcomes of 3D facial image superimposition techniques as related to the internal skeletal con guration. It has been shown that CBCT derived facial soft-tissue surface models are quite similar to those obtained by stereophotogrammetry 13,43,44 , allowing the assessment of changes in facial morphology in regards to standard reference structures, namely the anterior cranial base 3,4,8,18 . Thus, through the comparison with well-established anterior cranial base superimposition techniques 3,4,8,18 , the performance of the surfacebased techniques was thoroughly assessed.…”
Section: Discussionmentioning
confidence: 91%
“…Among others, this facilitates treatment decision-making and prediction of outcomes for ongoing or future interventions. The present study investigated, for rst time, various 3D facial surface superimposition areas in growing individuals and compared their applicability to those of a standard 3D anterior cranial base superimposition technique 4,8,21,25 , which has been previously validated 3,18,20 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations